’n Voorbeeld van die benutting van metafore in die maatskaplikewerk-hantering van seksueel gemolesteerde kinders (Deel 2) - Oelofse, M; Weyers, ML (Social Work/Maatskaplike Werk, 2002)
Back-ground: Due to the high incidence of child sexual abuse in South Africa and an increasing number of cases being reported to social worker institutions, practitioners have come under pressure to deliver more effective therapeutic services to especially the victims of such circumstances. Their interventions has, however, been hampered by two factors. They are the a bsence of well-grounded treatment programmes and a lack of therapeutic techniques and aids that would meet local needs . Objectives: To develop a treatment programme that could be used as a guideline for intervention and to determine the usefulness of metaphors as therapeutic tools in the application of this programme. Method: The research encompassed the establishment of a tentative treatment programme and its testing and refinement through multiple case studies . These cases covered more than 107 children that were allocated to the researcher while she was working at the Welcome Child Guidance Clinic between 1992 and 1999. The development and testing of metaphors formed an integral part of this process. The results that were obtained will be covered in two separate papers, one pertaining to the programme itself and the other to the use of metaphors. (Part Two) Results re the use of metaphors: Metaphors proved to be effective in the establishment of a therapeutic relationship, in helping children to cope with feelings of guilt and shame, and in addressing irrational thoughts and emotional pain. They are also useful in helping them to internalise new knowledge and insight, master new skills and develop a new feeling of self worth.